El nombre vernáculo del Aroma a Amaranthus Hybridus L. - Peláez, Citlali (2008)
In the Andean highlands from Ecuador to the Northwest of Argentina, at elevations of 1700 to 2900 m, an unidentified species known as “aroma” (Argentina), “sangorache” (Ecuador) or “ataco” (Ecuador and Peru) as its vernacular names grows spontaneously or is cultivated for its ethnobotanical use. In order to clarify its taxonomic status, the types of related species have been studied with numerical methods using morphological characters, suggesting that “aroma” belongs to Amaranthus hybridus L.